Revista e-Curriculum: origens e evolução de um periódico científico eletrônico na área de educação e currículo construído na colaboração pedagógica - Camas, Nuria Pons Vilardell (2008)
This study lies in the New Technologies and Education line of research and aims at describing and analyzing the process of producing an electronic journal on Education and Curriculum, by a group of students of the PhD Program of Postgraduate Education: Curriculum 2004 of PUC-SP. The work establishes a broad dialogue with several authors who reflect on the history of scientific publication, the evolution of magazines printed for the electronic media, especially the digital ones, the current principles of science for dissemination, the virtual reading, open access, and the curricular narrative. The instruments for collecting data were the researcher's field diary, the list of discussion created for the group of instructors from e-Curriculum magazine, recorded chats, recorded videos, testimonial e-mail of the subjects, letters of indexing organizations and a CD-ROM of the historical archives of e-Curriculum magazine. The research on the participatory action model provided the necessary engagement to hear the speeches of subjects who lived intensely the universe of the creation of a journal, enabling to confirm that, from the subject-authors perspective, the technological media are spaces of preparation and creation of new locations for the spread and dissemination of research, as spaces for learning socialization. The thesis shows that the electronic journals, in any area of knowledge, need to be explained through research for their existence. The investigation indicates that it is possible to create a journal in postgraduate programs and concludes that it is necessary to open up intense dialogues in these programs for the development of science in the country. It is not enough to produce magazines without their correspondent political-pedagogical effort for their use and effectiveness in the research domain. Finally, it was concluded that it is possible to construct a curricular narrative from the journey, from the search for the construction of pedagogical and social utopias, without losing or failing to develop the prescriptive curriculum